2015
DOI: 10.1111/aogs.12798
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid for preventing postpartum blood loss after cesarean delivery: a systematic review and meta‐analysis of randomized controlled trials

Abstract: Prophylactic TXA given before cesarean skin incision in women undergoing cesarean delivery, under spinal or epidural anesthesia, significantly decreases blood loss, including postpartum hemorrhage and severe postpartum hemorrhage, in addition to the standard prophylactic oxytocin given after delivery of the neonate. The effect of TXA on thromboembolic events and mortality as well as its use in high-risk women should be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 29 publications
3
91
1
4
Order By: Relevance
“…Nonetheless, more than 70% of procedures were elective C/S and thus there is an opportunity to further decrease exposure at delivery for planned procedures by considering routine use of antifibrinolytics or RBC salvage. Several randomized controlled trials have included patients receiving tranexamic acid prophylactically for C/S and have suggested that tranexamic acid is useful to reduce blood loss and RBCT . RBC salvage is also an option as its use in obstetrics has not been associated with increased risk of alloimmunization or amniotic fluid embolism …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, more than 70% of procedures were elective C/S and thus there is an opportunity to further decrease exposure at delivery for planned procedures by considering routine use of antifibrinolytics or RBC salvage. Several randomized controlled trials have included patients receiving tranexamic acid prophylactically for C/S and have suggested that tranexamic acid is useful to reduce blood loss and RBCT . RBC salvage is also an option as its use in obstetrics has not been associated with increased risk of alloimmunization or amniotic fluid embolism …”
Section: Discussionmentioning
confidence: 99%
“…This is not a uterotonic agent; TXA is an anti-fibrinolytic agent better known to gynaecologists for oral use as treatment of menorrhagia, and to trauma surgeons where it has been shown to reduce blood loss. 7 Topical application of tranexamic acid provides a high drug concentration at the site of the wound and a low systemic concentration. Studies from cardiac and orthopedic surgery have shown an equal or superior effect of topical compared with intravenous tranexamic acid on both bleeding and transfusion requirement.…”
mentioning
confidence: 99%
“…8 There are several published clinical trials for the use of TXA in the obstetric setting as well, but no consensus on its use or guidelines for management. 7 In the view of limited, good-quality evidence is available to inform on the best practices for prevention of bleeding at caesarean section due to placenta previa. Present study aimed at evaluating role of adjunctive IV Tranexamic acid versus topical Tranexamic acid infusion of the placental bed for prevention of postpartum haemorrhage in women with placenta previa.…”
mentioning
confidence: 99%
“…A systematic review (Simonazzi et al, 2016) confirmed that TXA can significantly decrease the incidence of PPH with an amount of blood loss >500 ml and severe PPH with blood loss > 1000ml. Consume of coagulation factors and platelets were reported in cases with severe postpartum bleeding.…”
Section: Exploratory Subgroup Analysesmentioning
confidence: 99%